2. PATHOGENIC DNA VARIATION WITHIN ACMG SECONDARY FINDINGS GENES IN 18, 000 HEALTHY INDIVIDUALS USING CLINICAL EXOME SEQUENCING FOR CARRIER SCREENING. (August 2019) - Mir Pardo, P.; Jiménez-Almazán, J.; Alonso, R.; Panadero, J.; Hernández-De-Diego, R.; Abellán, C.; Simón, C.; Martín, J.
Abstract : Introduction: Expanded carrier screening (ECS) programs aim to reduce the burden of recessive single-gene disorders by identifying the genetic risk for the offspring of individuals in reproductive age. ECS programs using Next Generation Sequencing (NGS) technology can get additional DNA variation in genes that may impact on individual's health. A significant group of clinically actionable genes are the secondary findings (SF) genes defined by the ACMG. Here, we describe the impact of pathogenic DNA variation in the SF genes providing evidence of additional useful clinical information for patients' health management. Material and methods: Retrospective analysis of sequencing data of 18, 364 individuals that underwent ECS for ART purposes from September 2015 to December 2018. Females represented the 51.7% (9, 488) of tested individuals whereas 8, 876 males accounted for the remaining 48.3%. Distribution between patients and gamete donors was 59.6% (10, 943) vs 40.4% (7, 421) respectively. DNA samples were sequenced in a NextSeq 500 system (Illumina) using a clinical exome kit evaluating 4, 800 genes (TruSight One sequencing panel; Illumina). Anonymized sequencing data were processed bioinformatically for a retrospective analysis focused on the 59 genes included on the ACMG recommendations for reporting of secondary findings (ACMG SFv2.0) (Kalia et al., 2016). Results: Based on Clinvar (Landrum et al., 2016) interpretation criteria, at least one pathogenic/likely-pathogenic variant associated to SF recommended for return was identified in 2% of the tested individuals (n=369). The distribution of positives findings between genders was: 176 males (2% of 8, 876) and 193 for females (2% of 9, 488). Likewise, the distribution of positives findings between ART patients and gamete donors was: 218 positive patients (2% of 10, 943), and 151 for donors (2% of 7, 421). In the retrospective analysis, a total of 238 unique pathogenic variants were detected. At least one variant was found in 33 (30 AD; 1 AR; 2 XL genes) of the 59 ACMG SF gene list. The most frequent pathogenic finding was the splice acceptor variant NM_000238.3:c.1946-2A>C in the KCNH2 gene (n=13), associated to QT long syndrome. The BRCA1 and BRCA2 genes were the most frequently positive called genes, with 75 unique pathogenic variants (31.5% of 238). Lynch syndrome associated genes were the second more frequently called positive genes, with 35 unique pathogenic variants distributed among the 4 analysed genes. Conclusions: The analysis of the ACMG SF genes provided evidence of pathogenicity for about 2% of the tested individuals with around 30% of positive cases associated to BRCA1 and 2 genes. Based on these results, analysis of SF genes can be optionally offered along with ECS, and patients willing to know this potentially useful information can have a benefit from it.